Incidence of a Capital Income Tax in a Growing Economy with Variable Savings Rates - Feldstein, Martin (Review of Economic Studies, 1974)
Journal Article Incidence of a Capital Income Tax in a Growing Economy with Variable Savings Rates Get access Martin Feldstein Martin Feldstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 4, October 1974, Pages 505–513, https://doi.org/10.2307/2296700 Published: 01 October 1974